Biochemical and nutritional attributes of Stevia rebaudiana grown in Pakistan - Jahangir Chughtai, Muhammad Farhan; Pasha, Imran; Sadiq Butt, Masood; Asghar, Muhammad (Progress in Nutrition, 2020)
Nutritional and health augmenting facets of Stevia rebaudiana as intense natural sweetener have been studied in different parts of world. Biochemical characterization of well adapted and well cultivated Pakistani Stevia have been carried out which is the need of hour to establish a better framework from nutritional viewpoint. Semi-arid conditions of central Punjab city, Faisalabad, have impacted the chemical composition that have been depicted in carbohydrates, crude protein, crude fat, crude fiber ash and moisture content as 63.59%, 10.64%, 5.47%, 7.60%, 8.75 and 3.95% respectively. Functional attributes have been well observed with slightly acidic to neutral pH 6.14, exhibits good swelling power, WHC, OHC, Bulk density. K, P, Mg, Na, Fe are found in maximum amount coinciding their ADI. Saturated, mono and polyunsaturated fatty acids like Palmitic, Palmitoleic, Stearic, Linoleic, Linolenic and Oleic have been identified in appreciable quantities like 28.31%, 2.17%, 2.39%, 13.65%, 25.48 and 4.95% respectively. FTIR mapping have concluded alcohols, alkanes, ketones, amines, esters, carboxylic acids, alkenes, hydroxyl groups as the major functional groups in raw powder and water extracts of Stevia. The study opens new horizons for further research covering safety aspects and steviosides characterization.